2013
DOI: 10.3109/08916934.2013.843672
|View full text |Cite
|
Sign up to set email alerts
|

The association between three promoter polymorphisms of IL-10 and inflammatory bowel diseases (IBD): A meta-analysis

Abstract: The IL-10 -819C/T and -592C/A polymorphisms contribute to susceptibility to UC, but IL-10 -1082G/A polymorphism neither associated with CD nor UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…Contrary to these, some studies reported that there are no significant differences in the allele and genotype frequencies of the IL-10-1082G/A polymorphism between IBD patients and controls in various populations [88,91,120]. Klein et al [91] reported that IL-10-1082G/A polymorphism is not demonstrably involved in the predisposition of IBD in German cohort.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Contrary to these, some studies reported that there are no significant differences in the allele and genotype frequencies of the IL-10-1082G/A polymorphism between IBD patients and controls in various populations [88,91,120]. Klein et al [91] reported that IL-10-1082G/A polymorphism is not demonstrably involved in the predisposition of IBD in German cohort.…”
Section: Discussionmentioning
confidence: 85%
“…Studies on the IL-10 promoter polymorphisms and IBD susceptibility have also been inconsistent [71,[83][84][85][86][87][88][89]. Some studies have found an associations between IL-10 polymorphism and IBD [71,86,87,90], whereas other studies were unable to find any association between IBD and the IL-10 promoter polymorphisms [83,84,88,91].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, most studies failed to find any association between IL10 promoter SNPs and susceptibility to develop IBD (Klein et al 2000;Koss et al 2000;Kim et al 2003;Balding et al 2004;Cantor et al 2005;Klausz et al 2005;Celik et al 2006;Sanchez et al 2009;Andersen et al 2010;Ahirwar et al 2012;Doecke et al 2013;Bank et al 2014;LopezHernandez et al 2015). Moreover, three meta-analysis, performed so far, were not consistent either, with each one showing associations of some of the three SNPs with one form of IBD that were not replicated by others (Zhu et al 2013;Lv et al 2014;Zou et al 2014). Interestingly, GWAS analyses did not find any evidence of association for those SNPs in IL10 promoter region with UC or CD (Barrett et al 2008;Franke et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Functional significance of these polymorphisms have been demonstrated both in vitro (Turner et al 1997;Tagore et al 1999) and in vivo (Ouma et al 2008), associating GCC haplotype with high, ACC with intermediate and ATA haplotype with low IL-10 production. A number of studies in different populations and three meta-analyses have addressed the association of one or more of these SNPs in IL10 promoter region with IBD, but the results were inconsistent (Zhu et al 2013;Lv et al 2014;Zou et al 2014). Thus, the role of these three common IL10 SNPs in IBD susceptibility, although probable, has not been elucidated yet.…”
Section: Introductionmentioning
confidence: 99%